The Impact of the Dimensions of the Strategic Role of Human Resources on the Level of Creativity in Jordanian Commercial Banks in the Northern Region (Global Journal of Science Frontier Research, 2021)
The study aimed at examining the impact of the three dimensions of the strategic role of human resources management namely planning polarization selection and recruitment on the creativity of commercial bank employees in Jordanian commercial banks One hundred five survey lists were analyzed as a sample for the study with a response rate of 88 98 percent that was valid for statistical analysis The study revealed a number of results the most important of which is the existence of a positive significant relationship between each of the following Human resource planning the dimension of human resource recruitment and the dimension of selection and appointment of human resources alone and the dependent variable creativity as well as positive and intrinsic dimensions with the three coefficients The study recommended supporting the dissemination of the spirit of creativity among all levels of management in commercial banks through training courses and supporting them with the necessary authorities to achieve this as well as encouraging them to suggest ideas that aim at improving their talents
Keywords: the strategic role of human resources - creativity – jordanian commercial banks